The Role of the Ecosystem Engineer, the Leaf‐Cutter Ant Atta cephalotes, on Soil CO2 Dynamics in a Wet Tropical Rainforest. Issue 2 (13th February 2019) - Fernandez‐Bou, A. S.; Dierick, D.; Swanson, A. C.; Allen, M. F.; Alvarado, A. G. F.; Artavia‐León, A.; Carrasquillo‐Quintana, O.; Lachman, D. A.; Oberbauer, S.; Pinto‐Tomás, A. A.; Rodríguez‐Reyes, Y.; Rundel, P.; et al.
Abstract: Leaf‐cutter ants are dominant herbivores that disturb the soil and create biogeochemical hot spots. We studied how leaf‐cutter ant Atta cephalotes impacts soil CO2 dynamics in a wet Neotropical forest. We measured soil CO2 concentration monthly over 2.5 years at multiple depths in nonnest and nest soils (some of which were abandoned during the study) and assessed CO2 production. We also measured nest and nonnest soil efflux, nest vent efflux, and vent concentration. Nest soils exhibited lower CO2 accumulation than nonnest soils for the same precipitation amounts. During wet periods, soil CO2 concentrations increased across all depths, but were significantly less in nest than in nonnest soils. Differences were nonsignificant during drier periods. Surface efflux was equal across nest and nonnest plots (5 μmol CO2 m −2 s −1 ), while vent efflux was substantially (10 3 to 10 5 times) greater, a finding attributed to free convection and sporadic forced convection. Vent CO2 concentrations were less than in soil, suggesting CO2 efflux from the soil matrix into the nest. Legacy effects in abandoned nests were still observable after more than two years. These findings indicate that leaf‐cutter ant nests provide alternative transport pathways to soil CO2 that increase total emissions and decrease soil CO2 concentrations, and have a lasting impact. Estimated total nest‐soil CO2 emissions were 15 to 60% more than in nonnest soils, contributing 0.2 to 0.7% to ecosystem‐scale soil emissions. The observed CO2 dynamics illuminate the significant carbon footprint of ecosystem engineer Atta cephalotes and have biogeochemical implications for rainforest ecosystems. Plain Language Summary: Leaf‐cutter ants modify their habitat to the extent that they are called ecosystem engineers. Living throughout the Americas, they construct massive nests to which they import the vegetation they harvest to feed a fungus they cultivate as their main food source. We studied the most common leaf‐cutter ant in Costa Rica to assess the impact of its nests on carbon dioxide (CO2 ) levels in surrounding soils and on soil CO2 emissions. In the Costa Rican rainforest, heavy rains easily clog the clayey soils, accumulating CO2 from microbial and root respiration. During wet periods, we observed lower CO2 concentrations in nest soils relative to nonnest soils. We attribute this difference to the nest structure, which provides ventilation for both nest CO2 and the CO2 originated in the surrounding soil. We also found that soil CO2 emissions were the same in nest and nonnest soils, but nest openings had emissions 100, 000 times greater. Consequently, nests and their surrounding soils emit 15 to 60% more CO2 than the equivalent nonnest soil areas. This difference, together with the expanding range of leaf‐cutter ants, favored by human activities and warmer climate, has implications with respect to the global carbon cycle. Key Points: Leaf‐cutter ant nests change the CO2 dynamics, reducing surrounding soil CO2 concentration and increasing total emissions For same precipitation amounts, nest soils accumulate less CO2 than nonnest soils; effects remain more than two years in abandoned nests Nest vents emitted up to 100, 000 times more CO2 than soil surface, and increased soil CO2 emissions at the ecosystem level by 0.2 to 0.7% El Rol de las Hormigas Cortadoras de Hojas en la Dinámica del CO2 en un Bosque Tropical Lluvioso: Las hormigas cortadoras de hojas modifican tanto su entorno que se las denomina ingenieros de ecosistemas. Son autóctonas de bosques y sabanas en América, aunque también infestan plantaciones agrícolas, y construyen hormigueros enormes donde transportan la vegetación recolectada. Pero las hormigas cortadoras de hojas no comen dicha vegetación, sino que la usan para cultivar un hongo que es la base de su alimentación. Investigamos a la hormiga cortadora de hojas más común de Costa Rica ( Atta cephalotes, allá conocidas como zompopas o arrieras) para evaluar el impacto que sus hormigueros tienen en los niveles de dióxido de carbono (CO2 ) en suelos adyacentes y en emisiones de CO2 . En el bosque húmedo de Costa Rica, las lluvias saturan la superficie de los suelos arcillosos, atrapando el CO2 producido por la respiración de microbios y raíces en la matriz del suelo. Durante los periodos más húmedos, observamos concentraciones de CO2 más bajas en suelos con hormigueros. Esta diferencia se debe a la estructura interna del hormiguero, que funciona como mecanismo de ventilación del CO2 producido tanto por las hormigas como por el suelo adyacente. También observamos que las emisiones superficiales de CO2 eran similares en suelos con o sin hormigueros, mientras que las emisiones provenientes de los orificios del hormiguero eran hasta 100 000 veces mayores. Esto significa que los suelos con hormigueros pueden emitir entre 15 y 60% más que suelos similares sin la presencia de hormigas. Esta diferencia, en conjunto con la expansión de estos insectos, que es favorecida por el impacto humano y el cambio climático, tiene implicaciones en el ciclo global del carbono.